Awareness and adherence to the Malaysian clinical practice guidelines for management of dengue infection in adults / Mohd Izhar Ariff - Mohd Izhar, Ariff (2018)
Dengue fever (DF) is a major public health dilemma globally. Currently Malaysia is experiencing a surge of dengue cases and increase in dengue mortality. Early detection and risk stratification for severe disease are crucial in the optimal management of dengue. In addition, prompt management and appropriate fluid management are also known to reduce dengue mortality. Malaysia Dengue Clinical Practice Guidelines (CPG) has been developed to provide evidence-based guidance in the management of dengue infection, but healthcare providers’ awareness and utilization as well as adherence to the Dengue CPG (revised 2nd edition) remain uncertain. Therefore, the aim of this study was to evaluate level of awareness and utilization of Dengue CPG among doctors in Malaysia and to evaluate the proportion of adherence to this Dengue CPG among the healthcare providers. This study was conducted in two phases. In phase one; a cross-sectional study was conducted among registered medical practitioners practicing at public or private Health Clinics and Hospitals in Malaysia. Doctors practicing only at hospital Medical and Emergency Departments were included, while private specialist clinics were excluded in this study. In phase two, a retrospective cohort study of dengue cases registered between 1 January 2014 to 1 June 2015 was conducted in public hospitals and health clinics in Selangor, Putrajaya and Kuala Lumpur. Adherence to the CPG recommendations were recorded by reviewing patient’s case notes. A higher percentage of doctors from public facilities (99%) were aware of the CPG compared to those in private facilities (84%). The proportion of doctors utilising the CPG were also higher (98%) in public facilities compared to private facilities (86%). The high proportions of doctors using the CPG in both public (97%) and private (94%) hospitals iv were also observed. However, only 69% of doctors in private clinics utilised the CPG compared to doctors in public clinics (98%). Overall proportion of adherence in clinical components of the recommendation were varies; (7.1 to 100.0% versus 7.7 to 73.8%) in history taking, (6.7 to 100.0% versus 12.3 to 60.0% ) in physical examinations, (18.4 to 100.0% versus 23.1 to 83.2% ) in assessment of warning signs, (0.6 to 100.0% versus 12.3 to 87.7%) in assessment of haemodynamic status, (60.0 to 100.0% versus 27.7 to 40.0%) in diagnosis, (46.6 to 80.0% versus 52.3 %) in case notifications, (73.2 to 100.0% versus 89.2 to 96.9 %) in performing specific laboratory investigations and (7.9 to 100.0 % versus 21.5%) in monitoring, for outpatient versus hospital settings respectively. Adherence trend were demonstrated to be higher in hospital settings compared to outpatient setting. Doctors in both public and private facilities were aware of the dengue CPG. However, most doctors in private clinic were less likely to utilise the CPG. Therefore, there is a need to increase the level of CPG utilisation especially in private clinics.